Socio-economic development and electricity access in developing economies: A long-run model averaging approach - Zhang, Tong; Shi, Xunpeng; Zhang, Dayong; Xiao, Junji (Energy policy, 2019)
Access to electricity continues to be a popular subject in empirical studies. However, the choice of key factors related to electricity access in the literature to date has been ad hoc due to the lack of a theoretical framework. This paper adopts a Bayesian Model Averaging (BMA) approach to selects important factors related to electricity access from 26 socioeconomic indicators using a sample of 48 developing countries, and reveal their long-term relationship with electricity access. The BMA approach allows us to identify the optimal empirical model when a theoretical foundation is not available. Moreover, it allows us to address the relative importance of variables using posterior inclusion probabilities and thus has clear policy relevance. Our results show that access to finance, education, economic development, infrastructure, and industrialisation are positively related to electricity access in the long-run. Although the long-run relationship does not indicate causality, it shows that to maintain this relationship, policy adjustments against any deviations from the relationship are needed. Our study suggests that electrification needs not only economic, educational and infrastructural development, but also private sector participation, governments’ commitment and political will, and integration with poverty reduction and other development schemes. •Relationship between electricity access and social-economic factors are studied.•Bayesian model averaging (BMA) approach is used to identify the long-run model.•Factors are ranked according to their posterior inclusion probabilities.•Policy adjustments are needed to maintain the long-term equilibrium relationship.